Native-speakerism policy in English language teaching revisited: Chinese university teachers’ and students’ attitudes towards native and non-native English-speaking teachers - Li (Evelyn) Wang; Fan (Gabriel) Fang (Cogent Education, 2020)
With the development of globalization, English continues to be widely used, and English teaching is given considerable importance. In recent years, Chinese universities have introduced more native English speakers as language teachers. However, the ingrained native-speakerism in the field of English language teaching (ELT) claims that native English-speaking teachers (NESTs) are the ideal English teachers, while non-native English-speaking teachers (NNESTs) are often marginalized. Recognizing the issue of native-speakerism in ELT, this paper investigates university students’ and teachers’ attitudes towards NESTs and NNESTs and towards the native-speakerism ideology. Findings obtained through a questionnaire and interviews at a university in southeast China show that stakeholders do not perceive a significant difference between the two kinds of English teachers and that NESTs cannot be deified merely due to their native-speaker identity. Native-speakerism, although generally accepted in the field of ELT, is not prevalent among the findings. This research attempts to raise the awareness of English learners and teachers regarding revisiting native-speakerism and provides several research implications on improving ELT practices in and beyond China.